Effects of membrane transport activity and cell metabolism on the unbound drug concentrations in the skeletal muscle and liver of drugs: A microdialysis study in rats - Shuyao Wang; Chun Chen; Chi Guan; Liping Qiu; Lei Zhang; Shaofeng Zhang; Hongyu Zhou; Hongwen Du; Chen Li; Yaqiong Wu; Hang Chang; Tao Wang (Wiley, 2021)
Abstract The unbound concentrations of 14 commercial drugs, including five non‐efflux/uptake transporter substrates-Class I, five efflux transporter substrates-class II and four influx transporter substrates-Class III, were simultaneously measured in rat liver, muscle, and blood via microanalysis. Kpuu,liver and Kpuu,muscle were calculated to evaluate the membrane transport activity and cell metabolism on the unbound drug concentrations in the skeletal muscle and liver. For Class I compounds, represented by antipyrine, unbound concentrations among liver, muscle and blood are symmetrically distributed when compound hepatic clearance is low. And when compound hepatic clearance is high, unbound concentrations among liver, muscle and blood are asymmetrically distributed, such as Propranolol. For Class II and III compounds, overall, the unbound concentrations among liver, muscle, and blood are asymmetrically distributed due to a combination of hepatic metabolism and efflux and/or influx transporter activity.